Career Gains and Identity Loss: The Effects of English in the Nepali Hinterlands - Khati, Ashok Raj (Journal of NELTA, 2014)
English in developing countries like Nepal has played a crucial role in increasing career and economic opportunities. It has provided access to the information and networks that are vital in building and maintaining economic links. On the other hand, there is an emerging issue of its threat to the local languages because of the massive use of English in different spheres of Nepalese lives. The major focus of the article is on how English has become instrumental in creating opportunities among multilingual communities and what perception these communities hold towards English and the development of local languages by incorporating the perspectives of EFL teachers from multilingual backgrounds and researcher’s own understanding of the context. The paper argues that English has unquestionably become instrumental in promoting career and economic opportunities, and the foremost reasons behind the decline of many local languages are more of political, cultural and economy guided in nature. DOI: http://dx.doi.org/10.3126/nelta.v18i1-2.10332 Journal of NELTA, Vol 18 No. 1-2, December 2013; 77-91